Missio Dei AND Communication in Pluralistic Society (Contextual usage of Social Communication in Furtherance of Missions) - Joel Samuel, C. (University of jaffna, 2018)
The global church has a mandate to accomplish the mission Dei mission of God, instituted by the Lord Jesus Christ. The Church along the history has tried its level best to satisfy it. However, in reality, the executing the mission of God by the church at large is seen as a threat by the contemporary pluralistic society. Though it is a universal issue, this research here confines its limit to the geographical boundaries of south Asia, as it is considered as the cradle of religions. A survey among the non-Christians was held to find out why the south Asian world considers Christianity as a threat. Apart from the generic concern on conversions, other key criticisms made on Christianity were the non- assimilation of local culture and the vocabulary used by Christians on the existing religious conventions. The research here picks up one of the stated causes for further study. It was about the vocabulary used by Christians in the social communications. It was found that certain communications by Christians does not respect the indigenous worship culture and faith of the pluralistic society. These are perceived, transmitted and understood, in a way against Christianity. It needs to be emphasized that any communication against local culture, disrespecting other faiths, elements of arrogance is not ethical by Christian norms. When Christian ethics are not exhibited, it limits the mission of God. The purpose of the research is to find why certain Christian leaders are not exhibiting Christian ethos in their social communication and how to transform them on their social communication ethics. As part of the research, it was evident that the Christian leaders who were not exhibiting Christian ethos are lacking social consciousness to a greater extent. Further study helped to understand that their Christian upbringing has not trained them on sociological perspectives. The solution for the discussed problem will be to educate them systematically on sociological reality and empowering them through intentional engagements. The author of the research paper is optimistic that it will definitely see a marked improvement in Christian communications which on the long run will help in accomplishing the mission of God.
Keywords: God’s mission; Religious disharmony; South asia; Social media; Fundamentalism; Intentional education